Essential Connections: Gender Equality and Social Inclusion within Agrifood Systems - Stepanovic, Serena; Ganira, Jedidah (World Vision, 2023)
World Vision, in partnership with FAO, led the development of a framework bringing together food security, nutrition and livelihoods alongside gender equality and social inclusion (GESI) principles—all supportive elements for ensuring transformative, inclusive development—that built on past exploratory research using a gendered lens to mainstream nutrition into agri-food systems. The resulting agri- food systems and GESI assessment methodology that operationalizes this framework aims to identify critical impact pathways that exist at the intersection of GESI domains (access, decision-making, participation, systems, well-being) and agri-food systems (food supply chains, food environments, consumer behavior) and associated drivers of change. Through an assessment of agri-food systems and GESI, gender and inclusion barriers and opportunities within these systems are identified and leveraged (where needed) to ensure the activity is or works to become GESI transformative. Since summer 2022, this approach has been piloted in five sub-Saharan countries and this will be expanded to Southeast Asia. Through this interactive capacity-strengthening session, we will first introduce the framework and assessment methodology, then through one of three distinct hands-on experiences, participants will then have the opportunity to apply the framework to their own activity/program (tailoring the assessment and queries that can support examination of these issues in their specific context and agri-food system) or through exploratory case studies involving select programs related to agri-food systems, climate, consumer behaviors and/or inclusive market-systems development